1999
DOI: 10.1093/nar/27.12.2457
|View full text |Cite
|
Sign up to set email alerts
|

NMR observation of T-tetrads in a parallel stranded DNA quadruplex formed by Saccharomyces cerevisiae telomere repeats

Abstract: We report here the NMR structure of the DNA sequence d-TGGTGGC containing two repeats of Saccharomyces cerevisiae telomere DNA which is unique in that it has a single thymine in the repeat sequence and the number of Gs can vary from one to three. The structure is a novel quadruplex incor-porating T-tetrads formed by symmetrical pairing of four Ts via O4-H3 H-bonds in a plane. This is in contrast to the previous results on other telomeric sequences which contained more than one T in the repeat sequences and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 20 publications
14
71
0
2
Order By: Relevance
“…These residues may form T-tetrads, similar to those previously observed in the center of a G-quadruplex structure, 24 and cap the ends of the G-tetrad core. Measurements of imino proton exchange times from external G-tetrads indicated the degrees of protection from solvent provided by these "caps".…”
Section: Novel Asymmetric Edgewise-looped Dimeric G-quadruplex Topolosupporting
confidence: 68%
“…These residues may form T-tetrads, similar to those previously observed in the center of a G-quadruplex structure, 24 and cap the ends of the G-tetrad core. Measurements of imino proton exchange times from external G-tetrads indicated the degrees of protection from solvent provided by these "caps".…”
Section: Novel Asymmetric Edgewise-looped Dimeric G-quadruplex Topolosupporting
confidence: 68%
“…[111,117,118] Stable mixed tetrads with more than one nucleobase type also form above the G-quartet. Patel et al showed that d(GCGGT 3 GCGG) dimerizes in solution to give a quadruplex with G:C:G:C tetrads stacked above the G-quartets.…”
Section: G-quartets Stabilize Stacking Of Nucleobase Triads and Tetradsmentioning
confidence: 99%
“…An average of 8 nt exists between each GGG run, and the intervening sequence may contain GG dinucleotides [47]; GG runs may contribute to quadruplex formation, albeit more weakly than GGG runs. Yeast telomere repeats form G4-DNA in vitro [48,49], although the types of G4-DNA structures formed by natural yeast telomere repeats have not been well characterized. The telomere 3' single strand overhang is short (~10-15 nt in G1, and up to 22 nt in S-phase) [50] and thus might have limited intramolecular quadruplex forming potential under most conditions.…”
Section: G-quadruplexes and Telomere Metabolismmentioning
confidence: 99%